2019
DOI: 10.1083/jcb.201811114
|View full text |Cite
|
Sign up to set email alerts
|

SGEF forms a complex with Scribble and Dlg1 and regulates epithelial junctions and contractility

Abstract: The canonical Scribble polarity complex is implicated in regulation of epithelial junctions and apical polarity. Here, we show that SGEF, a RhoG-specific GEF, forms a ternary complex with Scribble and Dlg1, two members of the Scribble complex. SGEF targets to apical junctions in a Scribble-dependent fashion and functions in the regulation of actomyosin-based contractility and barrier function at tight junctions as well as E-cadherin–mediated formation of adherens junctions. Surprisingly, SGEF does not control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 122 publications
3
43
0
Order By: Relevance
“…Crystal structure and quantitative binding data revealed that Scribble PDZ1 and PDZ3 domains display the highest affinity for the β-PIX PDZBM, whereas PDZ2 displays a 20-fold weaker affinity, and PDZ4 none [29]. Scribble also forms a ternary complex with Dlg1 and SGEF, a RhoG-specific GEF, at cell-cell junctions through the PDZ1 of Scribble and an atypical internal PDZBM in SGEF [45].…”
Section: Pdz Interactionsmentioning
confidence: 99%
“…Crystal structure and quantitative binding data revealed that Scribble PDZ1 and PDZ3 domains display the highest affinity for the β-PIX PDZBM, whereas PDZ2 displays a 20-fold weaker affinity, and PDZ4 none [29]. Scribble also forms a ternary complex with Dlg1 and SGEF, a RhoG-specific GEF, at cell-cell junctions through the PDZ1 of Scribble and an atypical internal PDZBM in SGEF [45].…”
Section: Pdz Interactionsmentioning
confidence: 99%
“…Métais et al, 2005;Navarro et al, 2005). In MDCK cells, Scrib knockdown reduces Ecad-based adhesion and Ecad retention at AJs, and delays polarization, potentially via effects on p120-Ecad interactions and the Rho-GEF SGEF (Awadia et al, 2019;Lohia et al, 2012;Qin et al, 2005). Scrib also regulates polarization of MCF7 cells in 3D cysts (Hendrick et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Our third hypothesis is that ARHGEF26 may have impacts on Salmonella invasion independent of its GEF activity. This is based on work from one of our labs that demonstrated that some of ARHGEF26's cellular roles involve forming a tertiary complex with DLG1 and SCRIB independent of nucleotide exchange (48). (49), as well as in regulating epithelial junctions formation, contractability, and 352 lumen formation in 3D cysts (48).…”
Section: Rhog Knockdown Does Not Phenocopy Arhgef26 Knockdownmentioning
confidence: 99%
“…This is based on work from one of our labs that demonstrated that some of ARHGEF26's cellular roles involve forming a tertiary complex with DLG1 and SCRIB independent of nucleotide exchange (48). (49), as well as in regulating epithelial junctions formation, contractability, and 352 lumen formation in 3D cysts (48). With this in mind, we investigated whether DLG1 and/or 353 SCRIB has a role in Salmonella invasion.…”
Section: Rhog Knockdown Does Not Phenocopy Arhgef26 Knockdownmentioning
confidence: 99%
See 1 more Smart Citation